A review on software quality models for learning management systems - Raja Ikram, Raja Rina; Thamilarasan, Yarshini; Osman, Mashanum; Salahuddin, Lizawati (Semarak Ilmu Publishing, 2023)
The objective of this paper is to review the basic software quality model and identify which existing software quality model and quality characteristics are suitable for Learning Management Systems. A literature review was conducted from the following sources - Science Direct, Scopus, and Elsevier. The search terms used are “online learning”, “basic software quality model” AND “learning management system”. The results of the literature review have identified five main software quality models commonly referred to in software quality literature – McCall, Boehm, FURPS, Dromey, and ISO 9126. In addition, ten common quality attributes for learning management systems identified are maintainability, portability, reliability, efficiency, usability, functionality, security, traceability, availability, and customizability. By identifying the most appropriate software quality model and characteristics for Learning Management Systems, this paper aims to provide guidance to developers and practitioners in the field of online learning to improve the quality and effectiveness of their systems.